Evaluation of foot kinematic structure by the order of bones' and joints' edges - Bani Hashim, Ahmad Yusairi; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Abdul Latif, Lydia (ACTA Press, 2011)
A number of distinct digital images can be formed if human foot is viewed as kinematic structure and later being converted into graphs. The synthetic images portray foot in shapes that are different from actual photographs or radiographs. The images exhibit the adjacency of bones, the incidence among bones and joints, and their paths. This study is done to find ways to represent foot in a different fashion and therefore computationally viable. The foot skeleton is studied and its structural kinematic representation is developed. This representation is later transformed into a graph. The kinematic structure is used to study the foot’s structure for engineering design viewpoints, whereas the graph is used to develop synthetic images so that foot conditions could be evaluated through pixels. This paper discusses and interprets foot conditions and anomalies. The method proposed is a one-dimensional mathematical model that is applicable in evaluating foot conditions.